Never been kissed [videorecording (DVD)] - Gosnell, Raja; Barrymore, Drew; Arquette, David; Vartan, Michael (Twentieth Century Fox Home Entertainment, 2003)
An undercover newspaper reporter in her early 20s is determined to go from "geek" to "chic" when she's sent back to high school to learn about today's teens.